Steroids pretreatment in assisted reproduction cycles - Sobotka, V.; Streda, R.; Mardesic, T.; Tosner, J.; Heracek, J. (The Journal of steroid biochemistry and molecular biology, 2014)
•Oral contraceptives prevent ovarian cysts during long GnRH agonist protocol.•Oral contraceptives assure regular period during long GnRH agonist protocol.•In GnRH antagonist protocol steroids support ovarian stimulation in low responders.•Steroids assess the cycle scheduling in GnRH antagonist protocol. The objective is to present an overview of trials and appreciate the relevant data on the effect of steroids pretreatment (oral contraceptives, 17β-estradiol and estradiol valerate) in assisted reproduction cycles. The subject of the study is to evaluate the clinical characteristics during steroids pretreatment cycles focused on the prevention of ovarian cysts, the positive contraceptive effect on the onset of regular period during long gonadotropin releasing hormone agonist protocol. In gonadotropin releasing hormone antagonist protocol the review is interested in supporting ovarian stimulation in low responders, the idea of cycle scheduling and improving treatment outcomes. The method is a review from MEDLINE/Pubmed database between 1994 and July 2012. We identified 15 randomised controlled trials (n=3069 patients). One trail (n=83 patients) assessed GnRH agonist protocol with or without steroids pretreatment, 8 trials (n=1884 patients) assessed GnRH antagonist protocols with or without steroids pretreatment and 6 trials (n=1102 patients) assessed GnRH antagonist protocols versus agonist ones with steroid pretreatment. Data demonstrates that oral contraceptives offer the effective prevention of functional ovarian cysts, the predictable onset of period during desensitisation. Existing data suggest that pretreatment with oral contraceptive pills or estradiol valerate give no advantage concerning number of oocytes or pregnancy rate. Pretreatment with oral contraceptive pills aiming to avoid weekend oocytes retrievals has to be more elucidated. In low responders oral contraceptive pill pretreatment may be beneficial in improving ovarian responses by reducing the amount of gonadotropins and the number of days required for ovarian stimulation. Current research indicates that also 17β-estradiol may be encouraging pretreatment in low responders and in cycle scheduling. This article is part of a Special Issue entitled ‘Pregnancy and Steroids’.